THE EFFECT OF LOW-DOSE INSEMINATION, SEMEN DEPOSITION SITES, INSEMINATION FREQUENCY AND AI TECHNICIANS ON BLUE FOXES - Jian-Ying Wang; Guo-Ping Zhang; Fu-Lin Tian; Huai-Ning Song; Gui-Sheng Wang; Xu-Kui Cui; Jin-Wen Wang; Ke Wang; Qing-Hua Huang; Zou-Ran Lan (Journal of Animal and Plant Sciences, 2015)
Artificial insemination (AI) technology is important to the economic benefits of blue fox vixens (Alopexlagopus). We studied the pregnancy results after AI with doses of 30, 50 and 70 million spermatozoa, the effect of semen deposition sites, insemination frequency and AI technicians in blue foxes. Compared with normal dose (70 million spermatozoa), low-dose inseminations (30 to 50 million spermatozoa) can achieve similar pregnancy rate, birth rate and mean litter size. However, deposition sites, insemination frequency and AI technicians influence the fertility of vixens. To achieve acceptable conception rate, we should deposit the semen into the uterine body, a minimum of two doses should be available each cycle. In conclusion, with excellent animal management, a dose of 30 million spermatozoa is enough to achieve satisfying pregnancy rates in blue fox vixens. We can use multiple intra-uterine inseminations in low-dose inseminations to achieve acceptable pregnancy results. Further investigation is needed to declare the minimum threshold number of spermatozoa for the best fertilization result.
Keywords: Artificial Insemination; Low-dose Insemination; Pregnancy Rate; Blue Foxes